“I Am Going to Take It Up”: Implementing Skin‐to‐SkinContact in Uganda - Karin Cadwell; Anna Blair; Kajsa Brimdyr; Kristin Svensson; Melissa Reyes; Mike Kagawa; Louise Racine Bastarache; Scovia Nalugo Mbalinda (Wiley, 2025)
Timely and prolonged skin‐to‐skin contact (SSC) immediately after birth is recommended in the Ugandan Clinical Guideline,the 2023 International Research and Practice Guideline on SSC and by the WHO/UNICEF Baby‐Friendly Hospital Initiative.Skin‐to‐skin contact is safe, low‐resource, evidence‐based and contributes to short‐ and long‐term health outcomes. However,practice is inconsistent. A rapid‐change intervention, PRECESS (Practice, Reflection, Education and training, Combined withEthnography for Sustainable Success), encouraged adaptation of the SSC Guideline protocol in a regional referral hospital inUganda. Fifteen key informants, including leadership and staff members, were interviewed before and after the practice changeabout perceived barriers and solutions for implementing SSC. The semi‐structured pre‐ and post‐intervention interviews wererecorded, transcribed and analyzed for meaningful units and themes. Three themes emerged: (1) Commitment to consistent,evidence‐based care within constraints; (2) Addressing knowledge and skill regarding the optimal practice of SSC; and (3)Willingness to “take‐up” the practice change for the benefit of mothers and babies. Our findings support the experientialmethod of practice change PRECESS to implement immediate, continuous, uninterrupted SSC for at least the first hour afterbirth. Despite the challenges and barriers identified in key informant interviews, significant progress was made in increasing theduration of SSC for both vaginal and cesarean births. The identified themes provide insight for future implementation of skin‐to‐skin contact
Keywords: breastfeeding | implementation | interview | low‐income setting | skin‐to‐skin contact | Uganda